2010
DOI: 10.1302/0301-620x.92b10.23578
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results of a metal-backed glenoid component in total shoulder replacement

Abstract: Total shoulder replacement is a successful procedure for degenerative or some inflammatory diseases of the shoulder. However, fixation of the glenoid seems to be the main weakness with a high rate of loosening. The results using all-polyethylene components have been better than those using metal-backed components. We describe our experience with 35 consecutive total shoulder replacements using a new metal-backed glenoid component with a mean follow-up of 75.4 months (48 to 154). Our implant differs from others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 47 publications
1
48
1
Order By: Relevance
“…It has been advocated in the litterature [6,7] that with increased lateralisation, the final active elevation would be decreased. This was not confirmed in our study, in which active elevation was comparable with the DELTA-type RSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been advocated in the litterature [6,7] that with increased lateralisation, the final active elevation would be decreased. This was not confirmed in our study, in which active elevation was comparable with the DELTA-type RSA.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors chose metallic lateralisation of the COR, which keeps the humeral bearing away from the pillar of the scapula. Several implants were designed according to this concept: the RSP (DJO Surgical, Austin, TX, USA) [16], the SMR (Lima, Udine, Italy) [5][6][7] and the Arrow RSA (FH Orthopedics, Mulhouse, France) [28,42]. In the latter, the design of the glenosphere and metal baseplate allows COR lateralisation of 8.5 mm.…”
Section: Introductionmentioning
confidence: 99%
“…They posited that the use of a screw construct, a fully coated bone in-growth surface at the bone interface and a low profile tray were critical factors in their improved survival. Likewise Castagna reported promising results in a series of 35 glenoids stabilized with screws and a large hallow central peg with a bone in-growth surface [44]. They had no patients who needed revision of their glenoid components during their follow up.…”
Section: Clinical Results For Glenoid Replacementmentioning
confidence: 99%
“…The results using all-polyethylene components have been better than those using metal-backed components. The results of 35 total shoulder replacements using a new metal-backed glenoid component with a mean follow-up of 75 months concluded that a metal-backed glenoid component was a good option in total shoulder replacement with results no worse than of those using a cemented all-polyethylene prosthesis (135).…”
Section: Total Shoulder Arthroplastymentioning
confidence: 99%